The Relationship Between Islam and Adat in Indonesia a Comparison Between Java and Minangkabau - Soehardi Soehardi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1997)
Islam has spread throughout Indonesia. since the thirteenth century, initially in Aceh and then gradually to the rest of Indonesia. Hitherto, nominally approximately 90% of the total population of Indonesia are Muslim. Presumably, the feature of the relationship between Islam and adat in Java and west Sumatra seems to be different. Here I shall compare the ethnic Javanese and the Minangkabau. The ethnic Javanese represent the majority population In Indonesia. Most consider themselves Muslims, but only a few conduct the Islamic sharia. On the other hand, the Minangkabau people are considered to be pious Muslim.